Antioxidant Bioactivity of Samsum Ant (Pachycondyla sennaarensis) Venom Protects against CCL4-Induced Nephrotoxicity in Mice. (3rd April 2014) - Ebaid, Hossam; Al-Tamimi, Jameel; Hassan, Iftekhar; Alhazza, Ibrahim; Al-Khalifa, Mohamed
Abstract : To assess whether SAV could influence the effects of carbon tetrachloride (CCL4 ) exposure, mice were treated with SAV in doses of 100, 200, 300 and 400  μ g/kg body weight and the effects on oxidative status and kidney function were studied. Serum levels of creatinine, malondialdehyde (MDA), and blood urea, together with renal and hepatic levels of MDA, glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT) were quantified in order to evaluate antioxidant activity. Results showed that the group injected with CCL4 exhibited significantly higher levels of oxidative stress markers, MDA, and significantly lower concentrations of GSH, SOD and catalase. SAV was found to significantly improve these oxidative markers, occasionally, in a dose-dependent manner. Furthermore, treatment with SAV was associated with the same behaviour in respect to kidney functions which had previously been impaired by CCL4 . Histopathological examination demonstrated that SAV, in different groups, improved the renal tissue damage induced by CCL4 and histological scores confirmed that significant improvements were obtained after treatment with SAV, particularly with the lowest dose (100  μ g/kg body weight). In conclusion, SAV has the potential capability to restore oxidative stability and to improve kidney functions after CCL4 acute injury.